2022
DOI: 10.1002/pri.1983
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact on adults and older people after hospitalization by Covid‐19

Abstract: Background and Objectives Hospitalization by Covid‐19 can cause persistent functional consequences after hospital discharge due to direct and indirect effects of SARS‐COV‐2 in several organs and systems of the body added to post‐intensive care syndrome and prolonged bed rest. These impacts can lead to dependency in activities of daily living, mainly in older people due to aging process and functional decline. This study aimed to compare the effects of hospitalization by Covid‐19 on functional capacity of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The included studies were conducted primarily in Europe (16 studies),19-34 with the remaining studies being completed in Asia (6 studies),35-40 South America (6 studies),14,41 and Africa (6 studies)42,43 (Table 1). Twenty-two studies were prospective cohort studies,14,19-27,29-33,35,37,39-43 and 4 were retrospective cohort studies28,34,36,38 (Supplemental Digital Content, Table 2, available at: http://links.lww.com/JACPT/A23).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were conducted primarily in Europe (16 studies),19-34 with the remaining studies being completed in Asia (6 studies),35-40 South America (6 studies),14,41 and Africa (6 studies)42,43 (Table 1). Twenty-two studies were prospective cohort studies,14,19-27,29-33,35,37,39-43 and 4 were retrospective cohort studies28,34,36,38 (Supplemental Digital Content, Table 2, available at: http://links.lww.com/JACPT/A23).…”
Section: Resultsmentioning
confidence: 99%
“…We acknowledge that the activity limitations and participation restrictions following hospitalization for COVID-19 infection reported in this review are similar to those observed during the first year following ICU care. 51,52 Of the 26 studies (1,878 participants) included in this review, 18 studies 14,19,20,22,[24][25][26][27][29][30][31]33,35,37,38,[40][41][42] with 1236 participants reported that 883 participants required ICU care. Therefore, about half of all individuals in the studies included in this review were critically ill and had the potential to develop post-intensive care syndrome (PICS).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations